Tantangan Perkembangan Pencak Silat di Kota Tangerang Selatan: Analisis Keterbatasan Fasilitas dan Pendidikan - Suwandi; Riska Putri (Innovations in Multidisciplinary Education Journal, 2024)
Pencak silat is a form of traditional martial arts that has high cultural and philosophical values in Indonesia. However, in South Tangerang City, the development of pencak silat faces significant challenges. This study aims to identify and analyze the obstacles faced in the development of pencak silat in this area, focusing on the lack of facilities and infrastructure as well as the lack of lesson time in schools. Through in-depth interviews with five figures from various martial arts institutions, namely Deni Asmara from Tapak Suci, Ahmad Maulana from Perguruan Silat Al Qoyyum, Fitrah Febri Salam from MS Jalan Enam Pengasinan, Gufron from Pencak Silat Padjajaran Cimande, and Delima Bungsu Andy, Chairman of IPSI Kota Tangerang Selatan, this research reveals that limited infrastructure and inadequate educational support are the main obstacles. The results of this study are expected to provide insights for stakeholders in formulating pencak silat development strategies in the city.